Research on FT-IR spectrum data mining of diesel engine lubricating oil. Issue 1 (April 2021) - Li, Jing; Tian, Hongxiang; Ming, Tingfeng; Sun, Yunling; Zhang, Shuai
Abstract: Aiming at the difficulties in quantitatively describing the pollution component information contained in FT-IR spectral data of diesel engine lubricants, wavelet transform and fractal box dimension are used to process FT-IR spectral data and get fractal dimension curve. Multiple peaks can be obtained by analyzing the curve. Two groups of lubricating oil samples with water content of 0.10%, 0.22%, 0.44% and 0.88% respectively and with ethylene glycol content of 0.10%, 0.22%, 0.44% and 0.88% respectively. For the above two groups of oil samples, the corresponding relation between peak position and contaminate ratio can be obtained, and a new method based on FT-IR prediction of contaminate ratio is feasible.